SUSTAINABLE DEVELOPMENT AND THE BUSINESS CONTEXT OF CSR BENEFITS ON THE POLISH MARKET - Ewa Stawicka (Acta Scientiarum Polonorum. Oeconomia, 2017)
This paper identifies the development of innovative, good practices in CSR and sustainable development in Poland in 2011–2016. In the researched years, it was found that the greatest number of practices were recorded in the area of social involvement and development of local communities, workplace and environmental practises. The conducted analyses show that in the Polish market in the context of sustainable development, there are emerging new business paradigms, innovative CSR strategies as SDG’s implementation to building the competitive advantage of companies. The effectiveness of CSR activities is difficult to measure. On the example of the analysed companies it can be stated that they shape the intangible as well as tangible value. The intangible values are the social capital and trust in the company, while the tangible values are savings and revenue growth.